Application of two dimensional thin layer chromatography pattern comparison for fingerprinting the active compounds in the leaves of vitex trifolia linn possessing anti-tracheospasmolytic activity. - Khatib, Alfi; Hoe, Arie C.; Selamat, Jinap; Sarker, Zaidul Islam; Jaswir, Irwandi; Verpoorte, Robert (Taylor & Francis, 2010)
We have developed one approach to fingerprint and estimate the active compounds in the leaves of Vitex trifolia Linn possessing anti-tracheospasmolytic assay using two-dimensional TLC pattern comparison. Based on the two-dimensional TLC pattern and the activity of the centrifugal partition chromatography fractions, we concluded that the semi polar compounds were responsible for anti-tracheospasmolytic activity. The best non-polar/semi polar mobile phases for the two-dimensional TLC using silica gel as the stationary phase were chloroform/methanol (9/1) as the first mobile phase and ethyl acetate/chloroform/methanol (28/28/44) as the second mobile phase.